Seroprevalence of toxoplasma gondii infection in cats from curitiba, paraná, Brazil - de Cruz, Marúcia Andrade; Ullmann, Leila Sabrina [UNESP]; Montaño, Patrícia Yukiko; Hoffmann, Juliano Leônidas [UNESP]; Langoni, Helio [UNESP]; Biondo, Alexander Welker (My University, 2011)
Toxoplasmosis is a worldwide zoonosis caused by the protozoa Toxoplasma gondii which infects all warm-blood vertebrates. This study aimed to assess the seroprevalence of anti-Toxoplasma gondii antibodies in a population of domestic cats seen at a major cat-only veterinary clinic in Curitiba, Paraná State, Southern Brazil. Serum samples were processed by indirect immunofluorescence assay (IIFA) for the detection of IgG. Antibody titers were found in 16.3% (46/282) of sera analyzed, with titers to T. gondii of 16 in eight cats, 64 in 23 cats, 256 in 14 cats and 1024 in one cat. Statistical differences were not found regarding the association with age, gender and different areas of the city (p > 0.05). No significant differences were found in any variable when comparing seropositivity with potential risk factors. The seroprevalence was relatively lower when compared to other Brazilian regions, probably due to the fact that the cats studied were owned, domiciled with restricted dietary habits based on processed foods, restricted access to the street and no prey access. In conclusion, low feline toxoplasmosis seroprevalence may be associated to owned cats due to adequate dietary care and restricted outdoor access, as well as low local environmental exposure.
Soroprevalência de infecção anti-toxoplasma gondii em gatos domésticos de curitiba, paraná, Brasil
Keywords: Cats; Indirect imunofluorescent antibodies test; Toxoplasma gondii